Association of Low-Density Lipoprotein Cholesterol With Risk of Aortic Valve Stenosis in Familial Hypercholesterolemia - Mundal, Liv J. (JAMA Cardiol, 2019)
IMPORTANCE: Aortic valve stenosis (AS) is the most common valve disease. Elevated levels of low-density lipoprotein (LDL) cholesterol are a risk factor; however, lipid-lowering treatment seems not to prevent progression of AS. The importance of LDL cholesterol in the development of AS thus remains unclear. People with familial hypercholesterolemia (FH) have elevated LDL cholesterol levels from birth and until lipid-lowering treatment starts. Thus, FH may serve as a model disease to study the importance of LDL cholesterol for the development of AS. OBJECTIVE: To compare the incidence of AS per year in all genetically proven patients with FH in Norway with the incidence of these diseases in the total Norwegian population of about 5 million people. DESIGN, SETTING, AND PARTICIPANTS: This is a registry-based prospective cohort study of all Norwegian patients with FH with regard to first-time AS between 2001 and 2009. All genotyped patients with FH in Norway were compared with the total Norwegian populations through linkage with the Cardiovascular Disease in Norway project and the Norwegian Cause of Death Registry regarding occurrence of first-time AS. Data were analyzed between January 1, 2018, and December 31, 2018. MAIN OUTCOMES AND MEASURES: Standardized incidence ratios. RESULTS: In total, 53 cases of AS occurred among 3161 persons (1473 men [46.6%]) with FH during 18 300 person-years of follow-up. Mean age at inclusion and at time of AS were 39.9 years (range, 8-91 years) and 65 years (range, 44-88 years), respectively. Total standardized incidence ratios were 7.9 (95% CI, 6.1-10.4) for men and women combined, 8.5 (95% CI, 5.8-12.4) in women, and 7.4 (95% CI, 5.0-10.9) in men, respectively, indicating marked increased risk of AS compared with the general Norwegian population. CONCLUSIONS AND RELEVANCE: In this prospective registry study, we demonstrate a marked increase in risk of AS in persons with FH.